Chemical composition and anticancer activity of Callistemon citrinus (Myrtaceae) volatile oil and active fraction (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Volatile oils have found use locally in the management of many diseases including tumor-related ailments. Due to the short-comings of orthodox medicine, there is a need to source for alternative drugs with better effects. Callistemon citrinus oil contains some bioactive compounds which are useful in treating many diseases. This study was designed to examine the chemical composition and cytotoxic efficacy of this plant oil.Method: Callistemon citrinus volatile oil was extracted from fresh leaves using a Clavenger apparatus by hydro-distillation method. Preliminary cytotoxic screening was carried out with brine shrimp at 10-1000 μg/mL. The essential oil was further tested on breast (AU 565) and cervical (HeLa) cancer cell lines at 50 μg /mL using MTT assay. Column chromatography of the oil was carried out and the resulting fractions subjected to biological testing. GCMS analysis was carried out on the oil and the most active fraction.Results: The oil produced concentration- dependent activity with an LC50 of 528.48 μg/mL in the brine shrimp mortality assay. The oil also produced -7.60 and +11.80 % inhibitions against HeLa and AU 565 cells respectively. Column fraction F1 produced the highest activity against AU 565 cells with 70.44 % inhibition and an IC50 of 15.96 μg/mL. C. citrinus oil revealed the presence of cineole (36.06 %) and α-pinene (21.41 %) as the major components while 1,1'-(5-hydroxy-2,2-dimethylbicyclo[4.1.0]heptane-1,7-diyl)bis-, (1α,5β,6α,7α)-ethanone (24.89 %.) was the most abundant in the active fraction.Conclusion: C. citrinus volatile oil has cytotoxic potential and is a good candidate for further in vivo studies.